2006
DOI: 10.1042/bj20061088
|View full text |Cite
|
Sign up to set email alerts
|

BI-D1870 is a specific inhibitor of the p90 RSK (ribosomal S6 kinase) isoformsin vitroandin vivo

Abstract: Hormones and growth factors induce the activation of a number of protein kinases that belong to the AGC subfamily, including isoforms of PKA, protein kinase B (also known as Akt), PKC, S6K p70 (ribosomal S6 kinase), RSK (p90 ribosomal S6 kinase) and MSK (mitogen- and stress-activated protein kinase), which then mediate many of the physiological processes that are regulated by these extracellular agonists. It can be difficult to assess the individual functions of each AGC kinase because their substrate specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
271
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(301 citation statements)
references
References 42 publications
22
271
0
Order By: Relevance
“…5C), suggesting that RSK activity is required for the phosphorylation during KSHV lytic replication. Because ORF45 is phosphorylated efficiently by RSKs (17), a shift in electrophoretic mobility of ORF45 attested to effective inhibition of RSK activity by BI-D1870, although no apparent change in phosphorylation of RSKs was observed as reported previously (54). These experiments confirmed that KSHV lytic replication induces rapamycin and U0126 doubly insensitive eIF4B phosphorylation that requires RSK activity.…”
Section: Orf45/rsk Axis Is Involved In Translation Regulation During supporting
confidence: 76%
“…5C), suggesting that RSK activity is required for the phosphorylation during KSHV lytic replication. Because ORF45 is phosphorylated efficiently by RSKs (17), a shift in electrophoretic mobility of ORF45 attested to effective inhibition of RSK activity by BI-D1870, although no apparent change in phosphorylation of RSKs was observed as reported previously (54). These experiments confirmed that KSHV lytic replication induces rapamycin and U0126 doubly insensitive eIF4B phosphorylation that requires RSK activity.…”
Section: Orf45/rsk Axis Is Involved In Translation Regulation During supporting
confidence: 76%
“…FMK blocks the ␣ 1 -adrenoceptermediated NHE-1 phosphorylation and stimulation in rat ventricular myocytes (29). On the other hand, BI-D1870 has been shown to be a potent ATP-competitive inhibitor of all p90 RSK isoforms (20). In this study, we found that FMK and BI-D1870 were equally effective in inhibiting OGD/REOX-mediated NHE-1 activation, implying a role for p90 RSK isoforms 1 and 2.…”
Section: Lack Of Nhe-1 Activation In Sm-dendrites Following Ogd/ Reoxsupporting
confidence: 51%
“…In contrast, the RSK inhibitor used in this study directly inhibited RSK kinase activity without influencing AngII-induced phosphorylation of RSK (Fig. 3A) (41).…”
Section: Angii Increased Phosphorylation Of Actin Filament-associatedmentioning
confidence: 80%